2005
DOI: 10.17660/actahortic.2005.691.16
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of Co2 and Temperature in Terms of Crop Growth and Energy Use

Abstract: In current greenhouse climate control, temperature set points follow a pre-set trajectory based on absolute or solar time parameters, adapted only to instantaneous and daily radiation. CO 2 is supplied during a well defined period of the day until a maximum concentration is reached. However, the rate of CO 2 supply is strongly limited by the heat demand, since flue gases are the most commonly used source of CO 2 . Interactions between effects of light, temperature and CO 2 concentration on photosynthesis and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 5 publications
(6 reference statements)
0
7
0
Order By: Relevance
“…During sunny periods, ventilation for cooling prevents high air humidity. With an increasing ventilation rate, CO 2 dosing becomes less efficient in maintaining the greenhouse CO 2 concentration above ambient conditions (Dieleman et al, 2005;Bakker et al, 1995). Ironically, it is under such conditions of high irradiation and high temperature where crop photosynthesis would benefit most from increased CO 2 concentrations (Morison and Lawlor, 1999).…”
Section: Conventional Greenhousementioning
confidence: 99%
“…During sunny periods, ventilation for cooling prevents high air humidity. With an increasing ventilation rate, CO 2 dosing becomes less efficient in maintaining the greenhouse CO 2 concentration above ambient conditions (Dieleman et al, 2005;Bakker et al, 1995). Ironically, it is under such conditions of high irradiation and high temperature where crop photosynthesis would benefit most from increased CO 2 concentrations (Morison and Lawlor, 1999).…”
Section: Conventional Greenhousementioning
confidence: 99%
“…To make more efficient use of temperature and CO 2 , an optimised climate control system was developed in which temperature and CO 2 were deployed such that energy use was minimised while maintaining crop production (Dieleman et al, 2005a). Firstly, the diurnal temperature course resulting in a predefined daily mean value was optimised while minimising the heat demand, based on the principles of temperature integration.…”
Section: Carbon Dioxidementioning
confidence: 99%
“…A modelling study with sweet pepper showed that this optimised control system reduced the energy use by 6% compared to a commercial cropping system, which was experimentally verified. The subsequent optimization of CO 2 supply, based on an algorithm that weighed the positive effect of CO 2 on production against the CO 2 loss by ventilation resulted in a simulated 2.5% higher production (Dieleman et al, 2005a).…”
Section: Carbon Dioxidementioning
confidence: 99%
“…Many growers maintain static air temperature set points, independent of ambient weather conditions outside [10]. Allowing the greenhouse temperature to rise above the desired mean daily temperature (MDT) when heating demand is low and fall below the desired MDT when heating demand is high, but maintain the same MDT, is another strategy to reduce energy use [11].…”
Section: Introductionmentioning
confidence: 99%